Brief report on the clinical characteristics of patients whose samples generate small cell lung cancer circulating tumour cell derived explants. (December 2020) - Vickers, Alexander J.; Frese, Kristopher; Galvin, Melanie; Carter, Mathew; Franklin, Lynsey; Morris, Karen; Pierce, Jacqueline; Descamps, Tine; Blackhall, Fiona; Dive, Caroline; Carter, Louise
Abstract: Introduction: Small cell lung cancer (SCLC) has a dismal prognosis. Circulating tumour cells (CTCs) can be used to generate CTC derived explants (CDX) for the study of SCLC biology and the development of novel therapeutics. We investigated whether there are demographic or clinical predictors of the success of CDX generation, and whether CDX models are representative of the SCLC patient population. Methods: This was a single centre, retrospective analysis of SCLC patients who had participated in the CHEMORES Study. Paired blood samples were donated for CTC enumeration and CDX generation attempt at pre-treatment baseline, disease progression and intervening timepoints. Clinical and demographic data was collected from electronic records, and analysed for differences between patients whose samples did and did not generate a CDX. Results: 231 paired blood samples were taken from 147 patients. 45 CDX were generated from 34 patients. CTC number was significantly higher in blood samples which successfully generated a CDX than those which didn't, at both baseline (p=<0.0001) and progression (p = 0.0001). The group with successful blood samples had a poorer performance status (p = 0.0067), and a higher proportion of patients with chemorefractory disease (p = 0.0077). Both progression free survival (PFS) (p = 0.0132) and overall survival (p=< 0.0001) were significantly shorter for patients with successful samples. Conclusions: Patients whose samples generate CDX models may have a higher disease burden and more aggressive disease. Thus, insights gained by study of SCLC CDX may have a significant impact, particularly in the SCLC subpopulation with the greatest clinical need.